Effect of amplitude and pulse in low frequency ultrasound on oil/water emulsions (2016)
The application of ultrasound within advanced or emerging technologies requires selecting parameters that depend on the target application. This study evaluated pulse and amplitude parameters of oil/water emulsions (20:80% w/w) using low frequency probe ultrasound equipment (20 KHz). A categorical multilevel factorial design was used with Design Expert® in which the following pulse treatments were defined: continuous, pulse 20:20 (on:off) and pulse 30:30 (on:off), for five minutes. Six amplitudes (30, 36, 42, 48, 54 and 60 μm) were evaluated for the following response variables: separation of phases in emulsion, temperature and accumulated power. The results showed that the best condition to obtain an emulsion with less phase separation was the 20:20 (on:off) treatment with an amplitude of 42 μm. The ultrasound probe application parameters that were obtained will enable the design of stable products from low-fat emulsions.